An Examination of Strategic Orientation and the Uses of Performance Appraisal in Singaporean Electronics Firms - Donald J Campbell; Kah Yie Foo (Asian Academy of Management Journal, 1997)
An Examination of Strategic Orientation and the Uses of Performance Appraisal in Singaporean Electronics Firms(PDF not available)